2004
DOI: 10.1124/mol.104.006072
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Independent Functions of Arrestins in the Regulation of Protease-Activated Receptor-2 Signaling and Trafficking

Abstract: The irreversible proteolytic nature of protease-activated receptor-2 (PAR2) activation suggests that mechanism(s) responsible for termination of receptor signaling are critical determinants of the magnitude and duration of PAR2-elicited cellular responses. Rapid desensitization of activated G-protein-coupled receptors (GPCRs) involves both phosphorylation and binding of arrestins. Arrestins also function as scaffolds and transducers of mitogen-activated protein (MAP) kinase signaling cascades. The PAR2 cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 36 publications
6
98
0
Order By: Relevance
“…We previously showed that activation of PAR1 results in transient ␤-arrestin association at the plasma membrane (28), whereas activated PAR2 and ␤-arrestin form a stable complex that co-internalizes to endocytic vesicles (21,29). Consistent with these studies, thrombinactivated PAR1 failed to remain associated with ␤-arrestin-2-GFP on endosomes in HeLa cells (Fig.…”
Section: Par1 Drives Heterodimer Constitutive Internalization-wesupporting
confidence: 76%
See 2 more Smart Citations
“…We previously showed that activation of PAR1 results in transient ␤-arrestin association at the plasma membrane (28), whereas activated PAR2 and ␤-arrestin form a stable complex that co-internalizes to endocytic vesicles (21,29). Consistent with these studies, thrombinactivated PAR1 failed to remain associated with ␤-arrestin-2-GFP on endosomes in HeLa cells (Fig.…”
Section: Par1 Drives Heterodimer Constitutive Internalization-wesupporting
confidence: 76%
“…The cDNA plasmids encoding N-terminally FLAG-tagged human wild-type PAR1, N-terminally FLAG-tagged PAR2, and C-terminal tail truncation mutants were described previously (20,21). The N-terminally HA-tagged PAR2 construct was generated and cloned into the pcDNA3.1 vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual signaling property of GPCRs has been reported for several receptors (35,48,(53)(54)(55)(56)(57)(58) and has given birth to the concept of biased agonists. This implies that a specific ligand might trigger distinct receptor conformations leading to different signaling pathways through interaction with different effector proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, for a surprising number of receptors phosphorylation is not required for arrestin binding. These include the lutropin receptor (Mukherjee et al, 1999a;Min & Ascoli, 2000;Min et al, 2002;Mukherjee et al, 2002), substance P receptor (Richardson et al, 2003), D6 non-signaling chemokine receptor (Galliera et al, 2004), orexin-1 receptor (Milasta et al, 2005), protease-activated receptor-2 (Stalheim et al, 2005), several splice variants of the serotonin 5-HT4 receptor , and leukotriene B4 receptor-1 (Jala et al, 2005). Although in some of these cases phosphorylation enhances the stability of the arrestin-receptor complex (Richardson et al, 2003;Milasta et al, 2005;Stalheim et al, 2005), arrestin binding to unphosphorylated receptors requires an explanation consistent with the known mechanism of arrestin activation.…”
Section: What Is Arrestin Looking For In a Gpcr?mentioning
confidence: 99%